2013
DOI: 10.1158/1541-7786.mcr-12-0456
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of TWIST1 Leads to Activation of Oncogene-Induced Senescence in Oncogene-Driven Non–Small Cell Lung Cancer

Abstract: A large fraction of non-small cell lung cancers (NSCLC) are dependent on defined oncogenic driver mutations. Although targeted agents exist for EGFR- and EML4-ALK-driven NSCLC, no therapies target the most frequently found driver mutation, KRAS. Furthermore, acquired resistance to the currently targetable driver mutations is nearly universally observed. Clearly a novel therapeutic approach is needed to target oncogene driven NSCLC. We recently demonstrated that the basic helix-loop-helix transcription factor T… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
83
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(90 citation statements)
references
References 47 publications
5
83
1
Order By: Relevance
“…Cell senescence plays an important role in cancer development and progression [48], and therapy-induced senescence (TIS) has emerged as a novel therapeutic approach for cancer eradication [42, 49, 50]. Several TIS pathways have been identified that induce cell senescence and the eradication of established tumors, such as inactivation of MYC, SKP2, or CK2 [51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Cell senescence plays an important role in cancer development and progression [48], and therapy-induced senescence (TIS) has emerged as a novel therapeutic approach for cancer eradication [42, 49, 50]. Several TIS pathways have been identified that induce cell senescence and the eradication of established tumors, such as inactivation of MYC, SKP2, or CK2 [51, 52].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, RC-6 induced some cells to give rise to cellular senescence. Previous studies indicated that p16, p21 and p27 are related to cellular senescence in senescence cells (49)(50)(51)(52)(53). Therefore, these proteins were determined in the present study.…”
Section: Senescence Characteristics In Nt2 Cells After Rc-6 Treatmentmentioning
confidence: 89%
“…Previous studies indicated that β-galactosidase activity is a major characteristic found in senescence cells and is generally applied to senescence detection (65)(66)(67). In addition, many studies have reported that p16 and p21 protein levels are increased in senescence cells (50)(51)(52)(53). At present, a small fraction of RC-6-treated NT2 cells can express β-galactosidase activity.…”
Section: Discussionmentioning
confidence: 99%
“…Emerging evidences have indicated that Twist1 played a crucial role in cancer initiation and progression through its ability to inhibit DNA damage-induced apoptosis and induction of the epithelial-mesenchymal transition (EMT) [13][14][15][16]. Suppression of Twist1 resulted in significant growth inhibition of multiple defined oncogenic drives-induced NSCLC [17]. In addition, silencing of Twist1 sensitized NSCLC cells to cisplatin via stimulating AMPK-induced mTOR/S6K1 inhibition which led to a decrease of Mcl-1 protein [18].…”
Section: Introductionmentioning
confidence: 99%